It's got to 'fit' - exploring corporate sponsorship decisions for festivals. (2016) - Smith, Wayne W.; Pitts, Robert E.; Litvin, Stephen W.; Mack, Rhonda W.
The sponsorship decision criteria for a local, but significant, non-sporting event is examined via in depth interviews and a grounded theory-based qualitative methodology. Transcripts of in depth interviews of the key sponsorship decision makers at 30 sponsoring firms across a range of business categories were systematically coded to identify sponsorship decision criteria. 29 of the 30 respondents mentioned 'fit' as a key criterion in the decision to sponsor. Further probing during the interviews revealed that the concept of 'fit' takes on multiple dimensions and meanings: 1) an altruism component of community goodwill and personal linkage; 2) a marketing component of both business-to-business and business-to-consumer; 3) an internal organisation component of employee relations and employee involvement were determined to be variations in the defining of the concept. Findings are discussed and directions for future research identified.